The sound pressure of an individual mode of a clamped-free annular plate - Rdzanek, W. P. (Archives of Acoustics, 2002)
The paper presents some theoretical results together with the corresponding numerical results of the directivity pattern of sound radiation of the clamped-free, free-clamped, and fully clamped annular plates. The results obtained are valid in the Fraunhoffer zone for some time-harmonic and axisymmetric processes. The results are compared for the three different plates of identical geometric and material parameters. The Kirchhoff-Love model of a~linear perfectly elastic plate is used. The data for the free-clamped plate are presented here for the first time, whereas the data valid for clamped-free and fully clamped annular plates are partially quoted from the literature. This new inventory of data makes it possible to perform some interesting comparisons of the magnitudes valid for the three different boundary conditions. All the data presented in this paper make the basis for some further theoretical investigations of the sound power of the three plates.